Report on the Treatment of the Insolvency of Natural Persons - Insolvency and Creditor/Debtor Regimes Task Force (World Bank, Washington, DC, 2014)
This report addresses the insolvency of natural persons following this structure: a first part introduces the objectives and nature of the report, deals with general issues, and describes the foundations of a system for the treatment of the insolvency of natural persons. The second part of the report analyzes the core legal attributes of system for the treatment of the insolvency of natural persons: within this system, the most relevant questions are analyzed in depth, namely the design of the system and the institutional framework, access to the system, the participation of creditors, the solutions to the insolvency process, and discharge. The main objective of this report is to provide guidance on the characteristics of an effective insolvency regime for natural persons and on the opportunities and challenges encountered in the development of such a regime. In this regard, the report raises awareness about the importance of a regime for the treatment of the insolvency of natural persons, and explores the advantages and disadvantages of the solutions to the numerous practical issues that have to be confronted in the design of an insolvency regime for natural persons.